2017
DOI: 10.1371/journal.pone.0175295
|View full text |Cite
|
Sign up to set email alerts
|

Fixational saccades are more disconjugate in adults than in children

Abstract: PurposeFixational eye movements are of particular interest for three reasons. They are critical for preventing visual fading and enhancing visual perception; their disconjugacy allows scanning in three dimensions, and their neural correlates span through the cortico-striatal, striato-collicular and brainstem networks. Fixational eye movements are altered in various pediatric ophthalmologic and neurologic disorders. The goal of this study was to compare the dynamics of fixational eye movements in normal childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…A recent study has shown that fixation in depth in healthy adults and children is quite stable and remains within these limits. 36 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that fixation in depth in healthy adults and children is quite stable and remains within these limits. 36 …”
Section: Discussionmentioning
confidence: 99%
“…A high-resolution video-based eye tracker (EyeLink 1000) was used as described in our previous work. 31,32 The experiment protocols complied with the tenets of the Declaration of Helsinki and were approved by the Cleveland Clinic Institutional Review Board. Written informed consent was obtained from the parents or legal guardians on behalf of all the children.…”
Section: Eye Movement Recordingsmentioning
confidence: 99%
“…The increase in fixation instability is detrimental to vision as shown by reduced visual acuity and reading speeds when simulating eye position instability [9,10]. Patients with amblyopia have an increase in fixation instability [11][12][13][14][15][16][17]. This instability could arise from the presence of nystagmus or due to increased amplitude of involuntary saccades and inter saccadic drifts elicited during fixation [18][19][20].…”
Section: Introductionmentioning
confidence: 99%